Effect Of Cerebrospinal Fluid Dynamics With Hydrocephalus In Porous Medium - et. al., B.Hemalatha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hydrocephalus is an excess of fluid in the cavities deep within the brain.It can lead to disturbances of the cerebrospinal fluid (CSF) flow in the hollow places of the brain. This paper presents a Mathematical model based on the principles of biofluid dynamics also this model predict the velocity of fluid flow along with its pressure and the amount of fluid tunneledtoanother body part using lumbar puncture throughout the brain ventricular pathways consistent with intracranial pressure measurements. We analyse the flow of hydrocephalus through porous medium of cerebrospinal fluid. Analytical results with respect to various parameters are presented graphically using MATLAB